Detailed renewable energy systems analysis-the case of Turkey in years 2023 and 2053 - Bölen, Hatice (My University, 2019)
Gelişen sanayii ve artan nüfus ile birlikte Dünyada ve Türkiye’de enerjiye talep artmaktadır. Birçok kurum ve kuruluş enerji taleplerini öngörebilmek için çalışmalar yapmaktadır. Günümüz enerji tüketimi göz önüne alındığında 2030 yılında enerji tüketiminin dünyada %60 ve Türkiye’de %100’den daha yüksek oranda artacağı belirtilmektedir. Bununla birlikte dünyada ve Türkiye’de nüfusun benzer olarak %1 oranında artması beklenmektedir. Söz konusu artan enerji talebinin dünyada başlıca sebebi artan nüfus ve gelişen ve büyüyen ekonomilerdir. Ülkemizde ise artan nüfusun yanı sıra esas olarak şehirleşme ve sanayileşmeden kaynaklanan bir enerji talebi artışı vardır. Gelişen ekonomilerdeki artan gelirler sonucu, araba sahipleri ve elektrik tüketimi artışı, enerjiye olan talebin yükselmesinin diğer nedenlerindendir. Bu çalışmada; genel olarak dünyada ve Türkiye’de enerji kaynakları incelenmiştir. Bu kaynaklardan elde edilen enerji üretimi ile enerji tüketim oranları kıyaslanarak, kurulu güç miktarları hakkında bilgi verilmiştir. Buna ek olarak, enerji sistemleri analiz modelleri detaylı şekilde incelenmiştir. Enerji analiz sistem modelleri kıyaslanmış olup; bu çalışma kapsamında, EnergyPLAN programının yenilenebilir enerji sistemleri modellemesinde daha uygun olduğu görülmüştür.

The demand for energy is increasing with the developing industry and growing population in the world and Turkey. Many institutions and organizations are working to predict energy demands. Considering today's energy consumption, it is reported that in 2030, 60% of the world energy consumption and 100% in Turkey are set to increase at a higher rate. However, the population in the world and Turkey is expected to increase by 1%. The main reason for this increasing energy demand in the world is the increasing population and developing and growing economies. In our country, in addition to the increasing population, there is an increase in the energy demand mainly caused by urbanization and industrialization. The increase in car owners and electricity consumption as a result of increasing revenues in developing economies is another reason for the increase in demand for energy. In this study, overall energy resources in the world and Turkey were examined. Energy production and consumption rates were compared and information was given about installed power capacities. In addition, energy system analysis models are examine in detail. Energy analysis system models were compared and EnergyPLAN program was found to be more appropriate for modelling renewable energy systems within the scope of this study.
Keywords: Energy Analysis; Enerji; Enerji Analizi Energy; Makine mühendisliği; Mechanical engineering; Renewable Energy; Yenilenebilir Enerji